2014
DOI: 10.1016/j.tjog.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Suitable timing of surgical intervention for ruptured ovarian endometrioma

Abstract: Comprehensive and early surgical intervention after endometrioma rupture can assist in excluding ovarian malignancy and can reduce the effects of cyst fluids, prevent adhesions, and preserve fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This complication can develop spontaneously, there are cases reported during menstruation [ 24 ] and periovulatory stages [ 25 ], but it more often occurs during pregnancy, after abdominal and pelvic trauma [ 26 ]. Also, the risk is higher when the diameter of endometrioma is ≥6cm [ 27 ]. Takami et al [ 26 ] reported a 2.8% incidence of the rupture of ovarian endometrioma during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…This complication can develop spontaneously, there are cases reported during menstruation [ 24 ] and periovulatory stages [ 25 ], but it more often occurs during pregnancy, after abdominal and pelvic trauma [ 26 ]. Also, the risk is higher when the diameter of endometrioma is ≥6cm [ 27 ]. Takami et al [ 26 ] reported a 2.8% incidence of the rupture of ovarian endometrioma during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there were no previous reports comparing the frequency of rupture of the ovarian cyst between its types. However, adhesion is more likely in endometrial cysts than other types of ovarian cyst , and decidualization during pregnancy can affect endometrial cysts resulting in softening to be more likely to rupture . Thus, endometrial cyst has the risk of rupture during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The rupture of an endometrioma is a rare event, with an estimated incidence of less than 3% among women of childbearing age who are known to have endometriomas ( 5 ) . This situation occurs more commonly during pregnancy, due to hormonal stimulation of endometrial stromal elements ( 2 ) , albeit with larger (≥ 6.0 cm) lesions ( 6 ) .…”
mentioning
confidence: 99%
“…The importance of the preoperative diagnosis is to support treatment strategies. Although some milder cases can be managed conservatively, there is a tendency toward greater use of early surgical exploration because of long-term undesirable effects of cyst fluid in the peritoneal cavity, such as adhesions, pelvic pain, and infertility ( 6 ) . In addition, the presumptive diagnosis of ruptured endometrioma, rather than ovarian neoplasms, facilitates the decision to perform laparoscopic exploration and allows the surgeon to perform the procedure with greater confidence.…”
mentioning
confidence: 99%